Processes controlling the aragonite saturation state in the North Yellow Sea near the Yalu River estuary: contrasting river input effects - Xu, Xuemei; Hu, Yingying; He, Zongcai; Wang, Xinyi; Chen, Hong; Han, Jianbo (Frontiers in Marine Science, 2023)
Understanding the characteristics of the aragonite saturation state (Ωarag) is necessary for assessing impacts of ocean acidification, especially in coastal oceans. Based upon surveys conducted in August and October 2022, the distribution and controlling processes of Ωarag were investigated in the North Yellow Sea near the Yalu River estuary. Surface water Ωarag values exhibited substantial variations of 1.14 to 3.79 for the input of river-diluted water and community production, whereas bottom water Ωarag values ranged from 1.82 to 2.40 in August. In addition, surface water Ωarag was further reduced to 1.07–2.37 in October due to the combined effects of seawater temperature decreasing and the upwelling of bottom water with low Ωarag values, while Ωarag values lowed to 1.04–2.14 in bottom water. Considerably low Ωarag values during summer and autumn in nearshore areas, especially in the Yalu River estuary, were resulted from the input of river-diluted water, while the net community respiration and remineralization induced the low bottom water Ωarag values in offshore areas. We suggest that integrated and multidisciplinary studies are required to quantify the trends and dynamics of acidification and its synergistic effects on the marine ecosystem in estuarine and coastal oceans.